2018
DOI: 10.30591/siklus.v7i2.897
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Aplikasi Stimulasi Tumbuh Kembang Terhadap Pengetahuan Ibu Dan Pertumbuhan Balita Umur 9 – 24 Bulan

Abstract: Menurut Global Nutrition Report tahun 2014, Indonesia termasuk salah satu negara yang memiliki tiga permasalahan gizi balita antara lain stunting, wasting dan overweight. Akibat dari permasalahan gizi pada balita yaitu adanya gangguan dalam perkembangan otak, gangguan kecerdasan, terhambatnya pertumbuhan fisik, serta gangguan proses metabolisme dalam tubuh. Rendahnya tingkat pengetahuan serta keterampilan orang tua tentang gangguan tumbuh kembang dapat menyebabkan terjadinya gangguan pertumbuhan dan perkembang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
2
0
2
Order By: Relevance
“…These study results align with other studies that have shown that smartphones are effective in health services because they are widely used, easy to carry, and can present information personally for communication, good information, and increase the users' knowledge 28 . This study is also in line with Khasanah's research, which has shown that the parents' role in monitoring children's nutritional status is essential.…”
Section: Effect Of the Use Of The Application On Knowledge Attitudes ...supporting
confidence: 90%
“…These study results align with other studies that have shown that smartphones are effective in health services because they are widely used, easy to carry, and can present information personally for communication, good information, and increase the users' knowledge 28 . This study is also in line with Khasanah's research, which has shown that the parents' role in monitoring children's nutritional status is essential.…”
Section: Effect Of the Use Of The Application On Knowledge Attitudes ...supporting
confidence: 90%
“…One aspect of mobile technology is smartphone devices (smartphones). Smartphone technology that is becoming a trend today is the existence of an Android-based operating system, so it is considered to be able to provide many conveniences and benefits for its users (Amaliah, 2018;Izah et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dan perkembangan adalah bertambahnya kemampuan struktur serta fungsi tubuh secara kompleks. Perkembangan melibatkan suatu proses diferensiasi jaringan, sel, organ dan sistem organ sedemikian rupa hingga dapat menjalankan masing -masing fungsinya (Hasyim & Saputri, 2021;Izah et al, 2018).…”
Section: Pendahuluanunclassified